The Vulnerability of Urban Communities to Flood Hazards In Tanzania: A Case of Dar es Salaam City - Hambati, Herbert (Tanzania Journal for Population studies and Development, 2014)
Losses from environmental flood hazards have escalated in the recent decades, prompting a reorientation of emergency management systems away from simple post-event response. The degree to which populations are vulnerable to flood hazards is not solely dependent upon proximity to the source of the threat or the physical nature of the hazard—social factors also play a significant role in determining vulnerability. This paper presents a participatory disaster risk method for assessing vulnerability in spatial terms using both physical and social indicators. It reveals that the most physically vulnerable places do not always spatially intersect with the most vulnerable populations. This is an important finding because it reflects the likely ‘social costs’ of hazards. While economic losses might be large in areas of high physical risk to floods, the resident population also may have greater safety nets (insurance, additional financial resources) to absorb and recover from the loss quickly. Conversely, it would take only a moderate hazard event to disrupt the well-being of the majority residents (who are more socially of vulnerable, but perhaps do not reside in the highest areas of physical risks to floods) and retard their longer-term recovery from disasters. This paper advances theoretical and conceptual understanding of the spatial dimensions of vulnerability. It further highlights the merger of conceptualizations of human-environment relationships with geographical techniques in understanding contemporary public policy issues.